1999
DOI: 10.1577/1548-8675(1999)019<0837:scosrt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Summer Counts of Stream-Resident Trout Can Differ between Daytime and Night

Abstract: We compared paired daytime and night counts of wild, resident brook trout Salvelinus fontinalis, brown trout Salmo trutta, and rainbow trout Oncorhynchus mykiss made by the same snorkelers within five stream reaches during August 1994. Reaches were 66-112 m long and had clear water, flows of 0.14-1.70 m 3 /s, and daytime water temperatures of 9-18ЊC. Each reach contained four habitat types: cascades, glides, pools, and riffles. Overall, we counted 109 trout in the daytime and 333 trout at night. Counts of trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…However, differences between electrofishing and night seining samples were not as extreme for juvenile Atlantic salmon. Like juvenile Atlantic salmon (see Fraser et al 1995;Gries et al 1997), both brook trout (see Walsh et al 1988;Gries et al 1997;Grost and Prendergast 1999) and brown trout (see Shuler et al 1994;La Voie and Hubert 1997;Grost and Prendergast 1999) are found above the stream substrate at night over a wide range of water temperatures. Additionally, brook trout (O'Connor and Power 1976;Walsh et al 1988) and brown trout (this study) can be captured at night using small, one-person seines and dip nets.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences between electrofishing and night seining samples were not as extreme for juvenile Atlantic salmon. Like juvenile Atlantic salmon (see Fraser et al 1995;Gries et al 1997), both brook trout (see Walsh et al 1988;Gries et al 1997;Grost and Prendergast 1999) and brown trout (see Shuler et al 1994;La Voie and Hubert 1997;Grost and Prendergast 1999) are found above the stream substrate at night over a wide range of water temperatures. Additionally, brook trout (O'Connor and Power 1976;Walsh et al 1988) and brown trout (this study) can be captured at night using small, one-person seines and dip nets.…”
Section: Discussionmentioning
confidence: 99%
“…Daytime observations were between 0900 and 1700 hours. Because day‐ and night‐time habitat use may differ (Heggenes et al , 1993; Gries et al , 1997; Grost & Prendergast, 1999), consecutive day‐ and night‐time surveys were conducted on five occasions, with snorkelling observations between 2300 and 0200 hours (1991, 1993 and 1997). The rivers are located north of the Polar Circle, and daylight was sufficient during part of the night dives, except in the large volume slow‐deep habitat which, to avoid comparative bias, was not included in the day and night surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Two experienced anglers fished the drift-dive reaches in each river during four 3-day trips over the period from late October to March (1998-99 Ugly River;1999-2000. All trout that were landed were tagged at the base of the dorsal fin with 100 mm long plastic dart tags (Hallprint Pty Ltd).…”
Section: Methodsmentioning
confidence: 99%
“…Direct methods of assessing the accuracy of underwater census, such as poisoning (Northcote & Wilkie 1963;Hillman et al 1992) or dewatering a reach after dives (Palmer & Graybill 1986) have indicated that a large proportion offish are usually missed by divers (30-80%). In small rivers, where electro-fishing is possible, diver counts have generally been lower than population estimates calculated from electro-fishing (Cunjak et al 1988;Hankin & Reeves 1988;Hayes & Baird 1994;Pert et al 1997;Grost & Prendergast 1999). This is particularly the case for juvenile trout in cold water where underwater counts can be below 10% of population estimates determined from electro-fishing (Gardiner 1984;Hayes & Baird 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation